Parental Choice and School Quality When Peer and Scale Effects Matter. - Shaughnessy, T (2007)
This paper presents a model of school choice with peer effects and scale economies within schools. Parents' perception of school quality depends on resources and on the characteristics of the student body. A network of local schools of uniform quality will be optimal, even though different households prefer different qualities. Whether schools of different qualities emerge depends on the strength of peer effects. If peer effects are strong there will be an incentive for existing schools to select for ability and for new selective schools--state-funded and private--to enter. To discourage bifurcation of the school system into different qualities, peer effects could be weakened, say by grouping students by ability within schools ("setting"; "streaming" or "tracking").